2012
DOI: 10.1371/journal.pone.0048113
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students’ Attitudes towards Overweight and Obesity

Abstract: ObjectiveStudies from the USA have identified medical students as a major source of stigmatizing attitudes towards overweight and obese individuals. As data from Europe is scarce, medical students’ attitudes were investigated at the University of Leipzig in Leipzig, Germany.DesignCross-sectional survey containing an experimental manipulation consisting of a pair of vignettes depicting an obese and a normal weight 42-year-old woman, respectively. Vignettes were followed by the Fat Phobia Scale (FPS), a semantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
47
2
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 54 publications
6
47
2
7
Order By: Relevance
“…In their study of health education students, Pantenburg et al. found that 98.9% of the students had a negative attitude toward obese people . Similarly, Stein et al.…”
Section: Discussionmentioning
confidence: 96%
“…In their study of health education students, Pantenburg et al. found that 98.9% of the students had a negative attitude toward obese people . Similarly, Stein et al.…”
Section: Discussionmentioning
confidence: 96%
“…Most previous studies examining pain judgments have asked participants to make ratings of text vignettes, 6,9,10,11 still images of patients, 8 or videos of computer-simulated patients. 30,31,56 Likewise, studies examining weight bias have tended to use text vignettes, 53,60 figure drawings, 24,28,72 or still images. 29,50,62,73,75 In contrast, participants in the current study rated videos of actual patients completing a standardized and highly relevant functional task.…”
Section: Discussionmentioning
confidence: 99%
“…11 Pantenburg B reported that 84% were of normal weight and 10% were either overweight or obese. 12 In present study, out of 100 female doctors, 52 (52%) female doctors were consuming pure vegetarian diet while 48 (48%) female doctors were consuming mixed (vegetarian and non-vegetarian) food. 32 (32%) female doctors were eating outside food >3 times a week while 68 (68%) female doctors were eating outside food <3 times in a week.…”
Section: Discussionmentioning
confidence: 54%